Results of an Innovative Program for Surveillance, Prophylaxis, and Treatment of Infectious Complications Following Allogeneic Stem Cell Transplantation in Hematological Malignancies (BATMO Protocol) - Malagola, Michele; Turra, Alessandro; Signorini, Liana; Corbellini, Silvia; Polverelli, Nicola; Masina, Lorenzo; Del Fabro, Giovanni; Lorenzotti, Silvia; Fumarola, Benedetta; Farina, Mirko; Morello, Enrico; Radici, Vera; et al. (Frontiers in Oncology, 2022)
Background. Infectious complications are a significant cause of morbidity and mortality in patients undergoing allogeneic haematopoietic stem cell transplantation (Allo-SCT). The BATMO (Best-Antimicrobial-Therapy-TMO) is an innovative program for infections prevention and management, and has been used in our centre since 2019. The specific features of the BATMO protocol regard both prohylaxis during neutropenia (abandonment of fluoroquinolone, posaconazole use in high-risk patients, aerosolized liposomal amphotericin B use until engraftment or a need for antifungal treatment, and letermovir use in CMV positive recipients from day 0 to day +100) and therapy (empirical antibiotics based on patients’ clinical history and colonization, new antibiotics used in second-line according to antibiogram with the exception of carbapenemase-producing K pneumoniae for which the use in first-line therapy is chosen). Methods. Data on the infectious complications of 116 transplant patients before BATMO protocol (Cohort A; 2016 - 2018) were compared to those of 84 transplant patients following the introduction of the BATMO protocol (Cohort B; 2019 - 2021). The clinical and transplant characteristics of the 2 Cohorts were comparable, even though patients in Cohort B were at a higher risk of developing bacterial, fungal and CMV infections, due to a significantly higher proportion of myeloablative regimens and haploidentical donors. Results. No change in the incidence of infections with organ localization was observed between the two Cohorts. A significant reduction in Clostridioides difficile infections by day +100 was observed in Cohort B (47% vs 15%; p=0.04). At day +30, a higher incidence of Gram negative BSIs was observed in Cohort B (12% vs 23%; p=0.05). By day +100 and between days +100 and +180, the incidence of BSIs and of the various etiological agents, the mortality from Gram negative bacteria, and the incidence of invasive fungal infections were not different in the two Cohorts. The incidence of CMV reactivations by day +100 dropped drastically in patients of Cohort B, following letermovir registration (51% vs 15%; p=0.00001).